ANALYSIS OF FARMERS' ATTITUDES AND SATISFACTION IN USING CERTIFIED POTATO (SOLANUM TUBEROSUM L.) SEEDS IN KARO DISTRICT - Relli Karosekali; Salmiah; Iskandarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The use of certified potato seeds is relatively very low because the price of seeds is expensive when compared to the prices of potato seeds made by the farmers themselves. The purpose of this study was to analyze the attitudes of farmers, farmers satisfaction, in using certified potato seeds in Karo District. The research method used is Fishbein multi-attribute to determine farmer attitudes, Customer Satisfaction Index (CSI) to determine farmer satisfaction levels and Importance Performance Analysis (IPA) to map attribute interests and performance. The results of the research on farmer attitudes were 176.45 with interpretations of liking to use certified potato seeds and a farmer satisfaction index of 76.74% with satisfied criteria while the results of the Importance Performance Analysis (IPA) analysis showed several attributes that needed to be maintained, namely resistance to pests and diseases, seed germination, yield selling price and temporary productivity that require attention are plant age, variety type, plant characteristics and seed size while attributes that need to be improved are seed price attributes, seed availability and seed labels.